The Impact of Online Education System at Student's and Teacher's During Covid-19 Pandemic in Pakistan - Hassan Karim; Manahil Hafeez (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the impact of the online education system on students and teachers during the covid-19 pandemic in Pakistan. The research method uses qualitative research, namely literature studies by examining the results of previous research related to the implementation of the existing education system in Pakistan. There are several research results to be studied, which provide a description of policies in the implementation of education during the covid-19 pandemic in Pakistan. Data analysis techniques use descriptive qualitative analysis, with reference to Miles & Hubberman's analysis, namely data reduction, data display, and conclusion drawing. The results showed that the online education system during the covid-19 pandemic in Pakistan, includes 1) learning that was temporarily interrupted due to the lack of technology actually provides challenges in solving problems faced by both teachers and students, 2) the readiness of online learning is expected to run effectively if there are clear guidelines / procedures, learning planning, self-efficacy and internal motivation, access services, especially online libraries, online communication, and significant online connectivity, 3) the Covid-19 pandemic is used as a challenge in the world of education to continue to provide maximum service in the midst of a crisis because education is closely related to the quality of human resources, and 4) Teachers can develop pedagogical innovations to fit the requirements of online learning where bringing conventional classes online. this study will help policymakers and the Ministry of Education in Pakistan to focus more on human resource development, interpersonal development, communication and technology management training, and support programs, especially for school teachers as the foundation of the next and future generations.